Meningkatkan Kemampuan Reading Comprehension Siswa SMA Negeri 1 Kebomas Melalui Extensive Reading - Lilik Sri Wahyuningsih (Jurnal Paedagogy, 2021)
This study aims to improve reading comprehension skills of SMA Negeri 1 Kebomas students through extensive reading. This research is a classroom action research conducted in three cycles by combining qualitative and quantitative methods. The sample of this research was students of class XI IPA 2 SMA Negeri I Kebomas. The research instrument used tests, observations, and questionnaires. The data analysis technique of this research is using descriptive analysis. The results of this study indicate that there is an increase in student reading comprehension learning outcomes as evidenced by an increase in test results during the study.